If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+3)*5=6x-105x+15=6x-1015+10=6x-5x
We move all terms to the left:
(x+3)*5-(6x-105x+15)=0
We add all the numbers together, and all the variables
(x+3)*5-(-99x+15)=0
We multiply parentheses
5x-(-99x+15)+15=0
We get rid of parentheses
5x+99x-15+15=0
We add all the numbers together, and all the variables
104x=0
x=0/104
x=0
| 1.8(5y+3)+5.6=29 | | 2=r-(-19) | | 3(w-2)-6w=6 | | 9a−5aa=7 | | s-9+31+s-50=180 | | 0.5(2c-3)-0.8c=2.7 | | 6h^2-2h-49=0 | | 2=r-(-19 | | 3(4x-1)-7x=2(x+4)+4 | | 12|9x+1|+4=148 | | 2(1−x)=11 | | 7w+82=180 | | (2x+4)=5x-5-2x | | (3n+7)^2=6n+14 | | 3x+10=-33 | | 63x59= | | z-20+37+z-9=180 | | 3/4x+12=4/3x | | x(-10)=90 | | 2m=-7=3(m+8) | | 2(5x-9)=6x+17 | | 65=–8x–15 | | w-19=47 | | 4x=+1220 | | 5+12=6x-10 | | 5(x-5)=10x-25-5x | | 16t^2=16t+480 | | 216=41-v | | 14-4c=28 | | 88=t | | -7.6+3.8=x | | 3+n-n/2-3/2=15 |